Implementation of Black Box Testing with the Application of Equivalence Partitioning Techniques in the M-Magazine Android Application at Semen Gresik High School - Frayudha, Angga Debby; Pande, Ivan Roy; Juwita, Mario Benson (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
This research aimed to improve the M-Magazine application at Semen Gresik High School to enhance its usability for students and teachers. The study focused on developing a digital platform called "mading" to improve the dissemination of information within educational institutions. The research addressed security issues and limitations associated with physical media by transitioning from traditional wall-mounted magazines to a digital format. The research followed a three-phase approach consisting of preparation, analysis, and implementation, which involved a literature review, data collection, system design, and testing. The resulting digital Magazine system offers a centralized platform for schools to manage and share information. Students can actively contribute by submitting content through the website. The system provides features to sort, filter, and publish information, ensuring timely and relevant updates. The findings demonstrated that the Digital Magazine effectively improves information dissemination in schools by providing better security, accessibility, and efficiency than traditional methods. This technology-powered platform empowers schools and students to share knowledge and stay informed.